Lentes sobre o corpo em cena : indícios da mobilização para a trajetória formativa - Mota, Reynaldo José Mascarenhas (2013)
This study intends, through the testimony of math teachers, to present the following question: What drives teachers of basic education to seek the extension project |Collaborative Group on Mathematical Modelling| (GCMM) of the State University of Feira de Santana (UEFS)? In this sense, the aim of this study was to understand the signs of mobilizing the bodies of mathematics teachers of basic education, which were part of the extension project GCMM between the years 2007 and 2012. In the methodology, I made use of a qualitative approach with case study. Data were collected through questionnaires, semi-structured interviews, the minutes of the meetings of the collaborative group, lattes curricula are presented, divided into behaviors observed during the meetings and the educational activities, taking into account the reaction of the teachers to the body. The research was conducted with eight (08) Basic Education teachers from public and private state of Bahia, of Feira de Santana and neighboring counties, members of the extension project GCMM, with an average age of 35 (thirty five) years for one year. The theoretical axes proposed for analysis refer to |Relationship to Know|, Charlot (2001, 2005), within the |Body Techniques| of Mauss (2003), Silva (2006), Fiorentini (2004) and Barbosa ( 2001) with |The Teaching and Learning of Mathematics and Modeling|. Thus, we assume that for the subject exists, it needs to have an awareness of the body in a physical, mental and social, appropriating a culture and building experiences in its history, through their relationship with time on what is |there and stay| in the contemporary world, in a continuous process, the field of his actions thus establishing a sense of relationship with the teaching, learning and knowledge. To that end, we list the learning process as a form of bodily reflections, with the understanding that the preliminary steps dissertation in relation to the body, human nature and transforming itself into cyclic motion. As the main result of our research we realized that for the population studied, in their reports, we should not take into account the fatigue of body and mind and the prestige of the profession, the more we consider the guy who thinks that there is amending its reality by their struggle to pursue what he believes the transformation of a better world through education. We can conclude that according to the teachers, the teaching profession is not enough to know. You have to invest, the challenges and obstacles inherent in the teaching profession, it is necessary and important to control the body and emotions.